The Effect of Sodium Bisulphite and Packaging Materials on Quality of Oyster Mushroom (Pleurotus ostreatus) in cold storage - Dodi Pratama; Ismed Suhaidi; Elisa Julianti (Universitas Sumatera Utara, 2013)
The aim of this research was to find the effect of sodium bisulphite concentration and packaging materials on the quality of oyster mushroom in cold storage. This research had been performed using factorial completely randomized design with two factors i.e. sodium bisulphite concentration (N): 1000 ppm, 2000 ppm, 3000 ppm and packaging material (K): no packaging, LDPE, polyprophylen, HDPE and plastic wrap. Parameters observed were moisture content, weight loss, protein content, fiber content, sulphite residue, values of colour, smell of sulphite, texture, and freshness. The result showed that sodium bisulphite concentration had highly significant effect on moisture content, weight loss, protein content, sulphite residue, values of colour, smell of sulphite, texture and freshness. The packaging materials had highly significant effect on moisture content, weight loss, protein content, fiber content, sulphite residue, values of colour and freshness. The combination of sodium bisulphite concentration and packaging materials had highly significant effect on moisture content, weight loss, and values of freshness and had no significant effect on protein content, fiber content, sulphite residue, organoleptic values of colour, smell of sulphite, and texture. Sodium bisulphite concentration of 1000 ppm and HDPE produced the best quality of oyster mushroom (Pleurotus ostreatus) in cold storage. .. Keywords : Oyster mushroom, sodium bisulphite, packaging materials